Numerical analysis of the influence of early fuel injection on charge motion in a direct injection spark ignition engine using scale-resolving simulations. (April 2020) - Theile, Martin; Reißig, Martin; Hassel, Egon; Thévenin, Dominique; Hofer, Martin; Michels, Karsten
This work summarizes the numerical analysis of the effect of early fuel injection on the charge motion in a direct injection spark ignition engine concerning cyclic fluctuations of the flow field. The combination of the scale-resolving turbulence model "Scale Adaptive Simulation" and post-processing routines for vortex trajectory visualization allows for a detailed insight into the temporal resolved and cycle-dependent behavior of the charge motion. In the first part, a simplified engine set-up is presented and used as a validation case to ensure correct behavior of the turbulence model and post-processing routines. In the second part, the computational fluid dynamics model of the real engine is introduced. The application of the proposed vortex tracking algorithm is shown, and a short discussion about the transient behavior of the charge motion in this engine set-up is given. The third part describes the analysis of the influence of the fuel injection on the charge motion at different engine speeds from 1000 to 3000 r/min and variations of the intake pressure from 1 to 2 bar. Finally, the impact on different flow field properties at possible ignition timings is discussed. Changes in mean flow field quantities as well as in aerodynamic fluctuations are found as a consequence of fuel injection.